Tissue Culture and Foliar Spray of Sulphate of Potash enhances productivity of banana - Mathiyalagan, P; Jeyaraj, C (Indian Farming, 2017)
Banana Productivity increased from 55 t to 125 t/ha by using tissueculture banana G-9 variety over traditional Robusta variety and foliarspray of 1.5% solution of SOP. The magnitude of increase withreplacement of tissue culture banana was 127% and the contribution of SOP towards yield increase was 25%. The net profit increased fromRupees 1,04,000 to 2,90,000/acre. This is a befitting success story of doubling the banana productivity and farmers income through new interventions i.e. introduction of tissue culture banana and foliar spray of SOP.